LITERARY AWARENESS AND THE READING EXPERIENCE: AN EVIDENCE-BASED ASSESSMENT - Chesnokova, Anna; Zyngier, Sonia (The Modern Higher Education Review, 2024)
In the Humanities, particularly in literature education, students’ responses to literary texts tend to be taken for granted. It is assumed that their ability to read and account for the reading experience does not require pedagogical intervention. Not only this is not a given, but any method or strategy used should be followed by evidence-based assessments to make sure they achieve the intended teaching learning objectives. Here we present a workshop on literary awareness conducted online in Ukraine in 2023 with forty-five participants and describe how it has been assessed. Despite the harsh conditions under which the participants were, ten pre-and post-tests and fifteen evaluation sheets were returned. The data of this pilot study was analysed quantitatively and qualitatively, and the results show that the objective of increasing participants’ sensitivity to the use of verbal patterns was achieved. These findings may stand as evidence to support a programme for sensitizing readers to literary texts.